(untitled) (Research, Society and Development, 2020)
The delimitation of PPAs is a fundamental requirement in several processes, such as the rural environmental registration, the environmental diagnosis, the environmental zoning and the environmental recovery plan. However, the implementation of legal definitions of PPAs is not a trivial task, depending on the detailed representation of the hydrographic network. This work deals with the data integration and the use of geoprocessing to obtain semi-automated Permanent Preservation Areas (PPAs)for the municipality of Santa Rosa de Lima-SC.. In order to delimit the hydrographic PPAs through Geographic Information Systems, it was necessary to generate a distance map (buffer) for each hydrographic feature. The specification of the buffer width is dependent on the type, width and size of drainage network features. The PPAs of springs were defined from 50 m, with the central point being the source. For the water courses, the PPAs are delimited in the marginal range from the regular channel, in horizontal projection with minimum widths ranging from 30 to 500 m wide. In considering the joining of all delimited PPAs - springs, watercourses, water bodies and wetlands - there are many overlapping areas. By joining all these areas, taking into account all overlaps, the resulting area is 10,125.04 ha, representing 50.12% of the area of the municipality. 76% of the hydrographic PPA delimited in this work is properly covered by forest vegetation.